The estate surveyors and valuers and the magic number: A point estimate or a range of value? - Aluko, Bioye Tajudeen; Ajayl, C. A.; Amidu, Abdul-Rasheed (International Journal of Strategic Property Management, 2010)
Property value is imprecise because of the imperfection of the property market. But, estate surveyors and valuers in Nigeria traditionally have continued to express this value as a single amount. This paper, therefore, attempts to examine the rationale behind this approach and the attendant problems associated with it. Besides, the paper, amongst other things, recommended that estate surveyors and valuers should expand the scope of their services beyond the confines of point estimates so that clients be informed as to the amount of possible deviation and the magnitude of risk in the value estimate through the adoption of statistical techniques.First Published Online: 18 Oct 2010